1990
DOI: 10.1038/hdy.1990.50
|View full text |Cite
|
Sign up to set email alerts
|

Clock mutations alter developmental timing in Drosophila

Abstract: The developmental time of period mutants in Drosophila melanogaster was monitored under different environmental conditions. We observed that the pe? mutants, which have short 19 h circadian cycles, develop faster from eggs to adult than the wild-type: perL mutants, which have long 28 h circadian rhythms, complete development more slowly than the wild-type. These results suggest that endogenous timers may be involved in regulating the development time of D. melanogaster.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
89
5

Year Published

1992
1992
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(105 citation statements)
references
References 27 publications
11
89
5
Order By: Relevance
“…In agreement with the predictions of the model, we observed a greater gate width of adult emergence in per L flies compared with per S flies (Fig.4C). It has, however, been previously reported that per S flies develop faster than per L flies (Kyriacou et al, 1990). This would, according to the first prediction of the model, imply a larger gate width in per S flies, in contrast to the observations, which instead are in agreement with the second prediction of the model.…”
Section: Discussioncontrasting
confidence: 56%
“…In agreement with the predictions of the model, we observed a greater gate width of adult emergence in per L flies compared with per S flies (Fig.4C). It has, however, been previously reported that per S flies develop faster than per L flies (Kyriacou et al, 1990). This would, according to the first prediction of the model, imply a larger gate width in per S flies, in contrast to the observations, which instead are in agreement with the second prediction of the model.…”
Section: Discussioncontrasting
confidence: 56%
“…In Drosophila, on the other hand, the development time from hatching to adult eclosion was 10-15 h shorter in mutants with a short (19 h) circadian period than in those with a long (29 h) one (Kyriacou et a!., 1990). In Neurospora, frq mutants did not alter the development time, but aprd mutant (formerly called frq-5 but in a different linkage group from that of frq) lowered the rate of the circadian clock by 4 h and delayed development by 60 per cent (Feldman & Atkinson, 1978).…”
Section: Discussionmentioning
confidence: 99%
“…In the most studied per mutants, the rates of several processes, i.e. the circadian rhythms controlling adult eclosion (Konopka & Benzer, 1971) and locomotor activity (Konopka & Benzer, 1971), shortterm fluctuations in the pulse frequency in males' courtship song (Kyriacou & Hall, 1980) and development time (Kyriacou et al, 1990) are altered by mutation in the per locus. These results suggested that the per locus controls the rate of some basic physiological process.…”
Section: Introductionmentioning
confidence: 99%
“…In insects, circadian clocks, which rhythmically regulate most behavioural and metabolic processes, have been implicated in the regulation of life history traits such as pre-adult development time (Kyriacou et al, 1990;Paranjpe et al, 2005) and adult lifespan (Miyatake, 1997a;Klarsfeld and Rouyer, 1998). Correlation between development time and circadian clocks was also reported in laboratory selection studies on melon flies (Miyatake, 1997b;Shimizu et al, 1997) and fruit flies (Kumar et al, 2006;Takahashi et al, 2013;Yadav and Sharma, 2013a).…”
Section: Introductionmentioning
confidence: 89%